Prevalence of oral soft tissue lesions and medical assessment of geriatric outpatients in North India - Sameer Rastogi; Pallak Arora; Shalini Kapoor; Sartaj Singh Wazir; Shirin Vashishth; Vandana Sharma (Wolters Kluwer Medknow Publications, 2015)
Introduction: Oral health reflects overall well-being for the elderly population. Compromised oral health may be a risk factor for systemic diseases commonly occurring in old age. Oral health evaluation should be an integral part of the physical examination, and dentistry is essential to qualify geriatric patient care. Aim: To determine the prevalence of oral soft tissue lesions and systemic diseases in institutionalized geriatric population in North India. Materials and Methods: Geriatric patients were clinically evaluated using a standard questionnaire and assessed for known medical illnesses and prevalence of oral soft tissue lesions. Four hundred patients (71% males and 29% females) with age ranging from 60 to 100 years were considered in the study group. Twenty-two (33.8%) patients were edentulous and seven patients (10.8%) were denture wearers. Forty-four (67.69%) patients reported with tobacco habits. Results: Most prevalent medical illness reported was diminished vision (15.5%), followed by hypertension (10%) and diabetes mellitus (6.25%). Several oral soft tissue lesions were reported among the study population. The most prevalent lesions were leukoplakia (12%), smoker's melanosis (10%), smoker's palate (9%), pigmentation on tongue (6%), frictional keratosis (5%), lichen planus (3%), denture stomatitis (2.5%), aphthous ulcers (2%), angular chelitis (1.5%), oral submucous fibrosis (1.5%), melanotic macule (1.5%), candidiasis (1.5%), irritation fibroma (1%), geographic tongue (1%), median rhomboid glossitis (1%), and traumatic ulcer (1%). Conclusion: The findings observed in this population are important and can have a determinant effect on the overall quality of life in this population. This information is a crucial prerequisite for health awareness programs involving the community health workers, oral physicians, and medical professionals.